2019
DOI: 10.7150/jbji.39050
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Prophylaxis for the Prevention of Surgical Site Infections in Orthopaedic Oncology - A Narrative Review of Current Concepts

Abstract: Abstract. The incidence of surgical site infections (SSIs) after elective tumour orthopaedic surgery in adults is higher than non-oncologic orthopaedic surgery. Their causative microorganisms and antibiotic susceptibilities are also different from the non-oncologic cases; with no apparent predictable microbiological patterns. Clinicians continue to struggle to tailor the optimal prophylactic regimen for the very heterogeneous group of tumour patients. Many clinicians thus prolong the first-and second-generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…The ischemic diabetic foot has many issues predicting an infection. High-grade open fractures are infected with nonfermenting gram-negative rods against which cefuroxime is not active (Gonzalez et al, 2014) and the optimal perioperative antibiotic prophylaxis in oncologic surgery is largely unknown (Müller et al, 2019). Furthermore, all three of these entities share a selection of antibiotic-resistant pathogens in common, due to frequent prior therapies (Wuarin et al, 2019), which motivated their exclusion for reasons of major inhomogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ischemic diabetic foot has many issues predicting an infection. High-grade open fractures are infected with nonfermenting gram-negative rods against which cefuroxime is not active (Gonzalez et al, 2014) and the optimal perioperative antibiotic prophylaxis in oncologic surgery is largely unknown (Müller et al, 2019). Furthermore, all three of these entities share a selection of antibiotic-resistant pathogens in common, due to frequent prior therapies (Wuarin et al, 2019), which motivated their exclusion for reasons of major inhomogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…However, a patient might have been included several times if the corresponding operations were entirely unrelated, e.g., a knee surgery for osteoarthritis in the first period, and a post-traumatic shoulder luxation in the second. Oncologic and diabetic foot surgeries were also excluded, because cefuroxime might be a suboptimal choice for these interventions (Uçkay et al, 2011;Müller et al, 2019;Gonzalez et al, 2014;Uçkay et al, 2019). The microbiological definition of deep SSI was based on the CDC criteria, requiring the presence of clinical infection (pus) and of the same bacteria in at least two intraoperative tissue samples (or of sonication samples) occurring within 30 days after the index surgery for soft tissue or within 1 year for implant-related SSIs (Mangram et al;1999).…”
Section: Study Criteria and Definitionsmentioning
confidence: 99%
“…Very recently, Muller et al 6 performed a literature review aiming to summarize the evidence for antibiotic prophylaxis in patients with musculoskeletal malignancies including STS, regardless of reconstruction type. They concluded that there was an enormous variety in the current clinical practices and a lack of adequate retrospective studies and evidence in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…5 Regarding the resection of truncal and extremity STS, the role of administration of antibiotics for prevention of wound complications is unclear. Muller et al 6 recently analyzed strategies used in different institutions and found highly heterogenous results noting that there is a large lack of evidence for any specific approach.…”
Section: Introductionmentioning
confidence: 99%
“…8 Like the non-oncologic patient, grampositive bacteria such as Staphylococcus aureus and methicillin-Resistant Staphylococcus aureus (MRSA) are considered common causative agents; however, gramnegative bacteria, especially non-fermenters (including Acinetobacter species, and Pseudomonas species), are more prevalent pathogens in some reports. 9,10 Although Corynebacterium diphtheriae (C. diphtheriae) is a rare etiology for SSIs due to high vaccination rates, 11 oncologic patients may be susceptible to invasive forms of cutaneous diphtheria secondary to altered immune responses. 8 Cutaneous diphtheria is usually complicated pre-existing cutaneous lesions, including traumatic abrasions, surgical wounds, burns, insect bites, pyoderma, eczema, impetigo, and dermatitis, which causes a breach in the skin surface 12,13 ; however, it also could be appeared on previously healthy skin.…”
Section: Introductionmentioning
confidence: 99%